Typha angustifolia L. Grass Hindering against Agricultural Productivity in Aliero River, Kebbi State, Nigeria - Aliero, Zubairu S.; Singh, Dharmendra; Keta, Jibrin N. (Journal of Sustainability and Environmental Management, 2022)
This research work tries to examine the socioeconomic impact of Typha angustifolia L. grass in parts of Kebbi state (Aliero, Kashin Zama and Sabiyal), Nigeria. For better understanding of the field conditions with regards to the impact of the grass on the socioeconomic of the area (agriculture, fishing and the livelihood pattern), two hundred (200) questionnaires were designed and administered, out of which only One hundred and forty five (145) were returned. Findings from the questionnaire survey of some communities along river Aliero (Kashin Zama and Sabiyal) show that, there is general reduction in the flow of water in the river channel over the last few years. This was attributed to blockages by Typha angustifolia L. grass and silt deposits within the river channel. There is also reduced or loss of cultivation of some crops particularly irrigated crops such as millet, maize, rice, wheat and vegetables, fishing activities in the area is also affected by the grass. This situation is worst in Kashin Zama area, where many farmers reported that, before the emergence of Typha angustifolia grass in the area, they recorded 225bags of rice in 10hecter, and now only 60-65 bags where recorded in the same piece of land. Moreover, communities have tried communal and individual manual clearance of the Typha, while Aliero Local Government, Kebbi State and Federal Governments are also carrying out mechanical clearance work in the channel. All these efforts have little impact.